MASJID TUA LANGGARA KABUPATEN ENREKANG: (Integrasi Nilai Islam, Tradisi Lokal, Arsitektur Dan Fungsi Sosial) - IRNO (Istiqra: jurnal hasil penelitian, 2025)
This study explores the forms of acculturation between local culture and Islamic values as manifested in the architectural design and social functions of the Langgara Old Mosque in Enrekang Regency. The mosque serves not only as a place of worship but also as a cultural center that reflects the harmonious integration of Islamic teachings and indigenous traditions. Employing a qualitative field research methodology supported by historical, archaeological, anthropological, and theological approaches, data were collected through direct observation, interviews, documentation, photovoice, and literature review. The findings reveal that cultural and religious acculturation is evident in the mosque's physical structure, which resembles the traditional Sapo Bottoa house; the use of local materials such as wood, bamboo, and ijuk; and the incorporation of Islamic symbols such as the dome and the bedug, which have undergone Islamization in meaning. Furthermore, the mosque functions as a cultural hub where community traditions such as Maccerang Manurung, Matammu Bulan, and Mi’cing Malillin Sola Mi’cing Mariwang are regularly practiced. These traditions not only preserve local cultural expressions but also embody Islamic values such as gratitude, unity, and spiritual reflection, positioning the mosque as a medium for the integration of belief and culture. These findings indicate that the Langgara Old Mosque symbolizes the resilience of local Islamic identity amid the pressures of modernization and globalization. Therefore, a structured revitalization of Tondon's traditional activities is necessary to institutionalize them as annual cultural programs that are educational, spiritual, and culturally reinforcing for the community of Enrekang Regency.